Factors contributing to jump heights in two-foot running jumps with and without a basketball - Jun Ming Liu; Antonia Zaferiou (Frontiers in Sports and Active Living)
IntroductionTwo-foot running jumps (TFRJs) are used by basketball players during games and evaluations for maximum jump height with or without a ball. Prior research on TFRJs performed by volleyball players revealed whole-body kinematics and kinetics variables that contribute to jump height, though it is unknown whether these variables contribute to jump height similarly in TFRJs performed by basketball players, and whether there are differences in how different variables relate to jump height in TFRJs. The objective of this study was to examine the correlation between jump height and whole-body kinematics and kinetics variables in both TFRJs with and without a ball.MethodsFifteen male and six female recreational to collegiate basketball players performed TFRJs with and without a basketball with the goal of jumping as high as possible toward an adjustable hoop. Variables of interest include initial forward center of mass (COM) velocity, the angle between a vector from the COM to the heel and horizontal (“plant angle”), COM ascent displacement, upward and backward impulses generated by the first and second legs, and net impulses generated (which also included downward impulse due to body weight).ResultsJump height had significant positive correlations with initial forward COM velocity, plant angle, COM ascent distance, and net backward and upward impulses in both TFRJs with and without a ball. Jump height also had significant positive correlations with backward and upward impulses generated by the first and second legs in TFRJs without a ball and with second leg upward impulse in TFRJs with a ball.ConclusionsTFRJs leveraged similar whole-body kinematic and kinetic mechanisms to achieve jump height as other types of running jumps from previous research. Therefore, athletes should aim to develop the physical and technical abilities through resistance training and specific practice support the use of the beneficial biomechanical variables in this study, such as being able to use more initial forward COM velocity, a shallower plant angle, a greater COM ascent distance, and greater overall impulse generation.